Apolipoprotein E2 (Arg-136→Cys), a variant of apolipoprotein E associated with late-onset dominance of type III hyperlipoproteinaemia - Feussner, Giso; Albanese, Marco; Mann, W. A.; Valencia, Alfonso; Schuster, H. (European journal of clinical investigation, 1996)
Type III hyperlipoproteinaemia (HLP) is usually associated with homozygosity for apolipoprotein (apo) E2 (Arg-158→Cys). We identified a 46-year-old white female with severe hyperlipidaemia and the heterozygous apo E3/2* phenotype. Typical clinical characteristics of type III HLP, i.e. palmar xanthomas (orange-yellowish discolorations of the palmar creases) and tuberoeruptive xanthomas, were present in the patient. Without therapy the patient's serum triglycerides (1.098 mg dL−1), cholesterol (546 mg dL-1), very low-density lipoprotein (VLDL) cholesterol (372 mg dL−1) and the apo E concentration (25.0 mg dL−1) were distinctly elevated as well as her VLDL cholesterol to serum triglyceride (TG) ratio at 0.34 (normal ratio about 0.2). Direct sequencing of polymerase chain reaction (PCR)-amplified segments of the apo ε gene identified a thymine for cytosine (C→T) exchange in the first base of codon 136 that is predictive for a Cys (TGC) for Arg (CGC) substitution in the encoded amino acid sequence. Two children, an 18-year-old female with the heterozygous apo E4/2* phenotype, a 25-year-old female with the heterozygous apo E3/2* phenotype and the 73-year-old father of the proband with the heterozygous apo E3/2* phenotype are also carriers of the rare mutant. The father has severe atherosclerosis and lipid values compatible with the diagnosis of type III HLP. The affected children have hyper/dyslipidaemia but as yet no clinical expression of the disease. We propose that in the analysed family this rare apo E2 (Arg-136→Cys) variant is associated with late-onset dominance of type III HLP.
Gesehen am 29.01.2025